(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Starting from the analysis of the Judgment no. 84/2016 of the Italian Con-stitutional Court, which declared inadmissible the questions as to constitutionality of articles 6, par. 3, and 13, pars 1, 2 and 3, of the Law no. 40/2004, this paper aims to clarify the complex category of not implanted embryos. Through these insights, it fur-ther outlines possible future destinations of not implanted embryos, underlining that they do not always imply «tragic choices» by representative legislator.